Head first PMP - Greene, Jennifer 1971-; Stellman, Andrew (Head first, 2018)
What will you learn from this book? Head First PMP teaches you the latest principles and certification objectives in The PMBOK® Guide in a unique and inspiring way. This updated fourth edition takes you beyond specific questions and answers with a unique visual format that helps you grasp the big picture of project management. By putting PMP concepts into context, you'll be able to understand, remember, and apply them-not just on the exam, but on the job. No wonder so many people have used Head First PMP as their sole source for passing the PMP exam. This book will help you: Learn PMP's underlying concepts to help you understand the PMBOK principles and pass the certification exam with flying colors Get 100% coverage of the latest principles and certification objectives in The PMBOK® Guide, Sixth Edition Make use of a thorough and effective preparation guide with hundreds of practice questions and exam strategies Explore the material through puzzles, games, problems, and exercises that make learning easy and entertaining Why does this book look so different? Based on the latest research in cognitive science and learning theory, Head First PMP uses a visually rich format to engage your mind, rather than a text-heavy approach that puts you to sleep. Why waste your time struggling with new concepts? This multi-sensory learning experience is designed for the way your brain really works.